Effect of the Natural Product Triptolide on Pancreatic Cancer: A Systematic Review of Preclinical Studies - Zhang, Chi; He, Xiao-Juan; Li, Li; Lu, Cheng; Lu, Ai-Ping (Frontiers in Pharmacology, 2017)
Objective: Triptolide (TL), a natural product isolated from Tripterygium wilfordii Hook F (TwHF), shows potent anticancer effects in vitro and in vivo. We aimed to summary the biochemical mechanisms through which TL has been shown to induce apoptosis, autophagy and inhibit angiogenesis in pancreatic cancer (PC). Methods: We undertook a systematic review of preclinical evidence. We searched electronic databases. The potential mechanisms and the underlying signaling pathways have been accumulated as well. Results: We screened 116 abstracts for eligibility and included 17 preclinical studies in the analysis. Details of the animals and cell lines were provided in 16 studies (94.1%). Six studies (75.0%) randomly assigned animals to treatment or control groups and only 1 study (12.5%) reported on blinding. The majority of the TL's research field has focused on its pro-apoptotic effects through downregulation of inhibitory pathways and upregulation of apoptotic pathways. The studies have shown that TL is effective both in vitro and in vivo against PC cells. Conclusion: This study provides a systematic summary of TL’s anti-pancreatic cancer profile and the underlying mechanisms of with special emphasis on the apoptosis, autophagy, angiogenesis and related molecular pathways. Improved study quality in terms of treatment allocation methods reporting, randomization and blinding will accelerate needed progress towards trials.